SPEKTRUM SYMBOL DAN STRUCTURE SENSE MATEMATIKA SISWA MADRASAH TSANAWIYAH - Hamdan Sugilar; Rahayu Kariadinata; Nunung Sobarningsih (KALAMATIKA Jurnal Pendidikan Matematika, 2019)
The purpose of this study is to determine the symbol sense and structure of mathematical sense in terms of students' ability to solve algebraic problems or other mathematical problems that require symbol expression or structure. Difficulties experienced by students in solving mathematical or algebraic problems may be due to the ability of symbol sense and low structure sense or didactic design that the teacher conveyed is not in accordance with the category of symbols and structure sense that students have. A student with good symbols and structure sense is able to appreciate the power of symbols, knowing when to use the right symbols and being able to manipulate and understand symbols in various contexts. The method used in the study used a qualitative descriptive method. The population of this study was seventh grade students of the Islamic junior high school, the instruments used were symbol and structure sense tests, questionnaires, and interview forms. The results of the study indicate that the ability of symbol sense and student structure sense is still low because of a lack of conceptual knowledge and algebraic manipulation, for this reason it is necessary to have an appropriate learning model to improve both of these abilities.